Association of bilateral oophorectomy and menopause hormone therapy with mild cognitive impairment: the REDLINC X study. (4th March 2022) - Blümel, J. E.; Arteaga, E.; Vallejo, M. S.; Ojeda, E.; Meza, P.; Martino, M.; Rodríguez-Vidal, D.; Ñañez, M.; Tserotas, K.; Rojas, J.; Rodrígues, M. A.; Espinoza, M. T.; et al.
Abstract: Background: Dementia is a major public health problem. Estrogen is a regulator of the central nervous system and its deficit could be involved in cognitive decline in older women. Objective: This study aimed to evaluate the association of bilateral oophorectomy, menopause hormone therapy (MHT) and other factors on mild cognitive impairment (MCI). Method: The case–control study included 941 otherwise healthy postmenopausal women aged 60 years and over from six Latin American countries. Personal and family data were recorded and MCI was assessed using the Montreal Cognitive Assessment test (MoCA). Results: Average age, years of education and body mass index were 66.1 ± 5.8 years, 12.4 ± 5.0 years and 26.0 ± 4.3 kg/m 2, respectively. A total of 30.2% had undergone bilateral oophorectomy and 40.3% had used MHT. A total of 232 women (24.7%) had MCI. The prevalence of MCI was higher in women with intact ovaries and non-MHT users as compared to MHT users (29.3% vs. 11.7% [odds ratio (OR) 0.32; 95% confidence interval (CI) 0.20–0.51]). Among oophorectomized women, MCI prevalence was higher among non-MHT users as compared to MHT users (45.2% vs. 12.8% [OR 0.18; 95% CI 0.10–0.32]). Logistic regression analysis determined that the variables associated with MCI were age >65 years (OR 1.69; 95% CI 1.20–2.38), parity (having >2 children; OR 1.69; 95% CI 1.21–2.37), bilateral oophorectomy (OR 1.56; 95% CI 1.09–2.24), hypertension (OR 1.41; 95% CI 1.01–1.96), being sexually active (OR 0.56; 95% CI 0.40–0.79), education >12 years (OR 0.46; 95% CI 0.32–0.65) and MHT use (OR 0.31; 95% CI 0.21–0.46). Conclusion: Age, parity, bilateral oophorectomy and hypertension are independent factors associated with MCI; contrary to this, higher educational level, maintaining sexual activity and using MHT are protective factors.